Maintaining Specimen Integrity for G6PD Screening by Cytofluorometric Assays. (June 2015) - Kahn, Maria; Ward, Walter H. J.; LaRue, Nicole; Kalnoky, Michael; Pal, Sampa; Domingo, Gonzalo J.
Cytochemical staining remains an efficient way of identifying females who are heterozygous for the X chromosome-linked glucose-6-phosphate dehydrogenase ( G6PD ) gene. G6PD is highly polymorphic with certain alleles resulting in low intracellular G6PD activity in red blood cells. Low intracellular G6PD activity is associated with a risk of severe hemolysis when exposed to an oxidative stress such as fava beans, certain drugs and infections. Heterozygous females express the enzyme from both X-chromosome alleles resulting in two red blood cell populations each with G6PD enzyme characteristics representative of each allele; for example, normal and deficient. Cytochemical staining is the only way to determine the relative representation of each allele in red blood cells, a feature that is critical when assessing the risk for severe hemolysis when exposed to an oxidant such as the anti-malarial drug primaquine. This letter discusses red blood cell integrity with respect to the cytofluorometric assays for G6PD activity. An approach to making this test more robust is suggested. The approach makes this test more reliable and extends its use to a broader range of blood specimens.